2014
DOI: 10.1088/1468-6996/15/1/015004
|View full text |Cite
|
Sign up to set email alerts
|

Studying nanostructure gradients in injection-molded polypropylene/montmorillonite composites by microbeam small-angle x-ray scattering

Abstract: The core–shell structure in oriented cylindrical rods of polypropylene (PP) and nanoclay composites (NCs) from PP and montmorillonite (MMT) is studied by microbeam small-angle x-ray scattering (SAXS). The structure of neat PP is almost homogeneous across the rod showing regular semicrystalline stacks. In the NCs the discrete SAXS of arranged crystalline PP domains is limited to a skin zone of 300 μm thickness. Even there only frozen-in primary lamellae are detected. The core of the NCs is dominated by diffuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…These blind areas have partly been filled exploiting the four‐quadrant symmetry of SAXS patterns with fiber symmetry. Data for the remaining “cheese holes” have been extrapolated assuming that SAXS patterns do not show sharp reflections which might hide in such a hole .…”
Section: Methodsmentioning
confidence: 99%
“…These blind areas have partly been filled exploiting the four‐quadrant symmetry of SAXS patterns with fiber symmetry. Data for the remaining “cheese holes” have been extrapolated assuming that SAXS patterns do not show sharp reflections which might hide in such a hole .…”
Section: Methodsmentioning
confidence: 99%
“…In 2014, Stribeck et al observed the properties of injection-molded polypropylene (PP)/MMT composites by microbeam small-angle X-ray scattering [97]. They were interested in studying gradient effects along the radius of injection-molded nanocomposite rods.…”
Section: Years 2010-2014: Interface Chemistry Of Smpincs Leads To Enhmentioning
confidence: 99%
“…These approaches hold tremendous promise for understanding morphological phenomena in SMPINCs. Reprinted from Stribeck et al [97], Copyright 2014, Open Access Fig. 7).…”
Section: Years 2010-2014: Interface Chemistry Of Smpincs Leads To Enhmentioning
confidence: 99%
“…19 Mae et al have observed that the elastic modulus and the strain values of iPP/SiO 2 composites modified with poly(styrene-b-ethylene-co-butylene-b-styrene) (SEBS) have depended on the selectivity of SiO 2 nanoparticles, i.e. 25 Although SEBS elastomer was widely applied as a compatibilizer for polymer blend systems, its application as impact modifier and compatibilizer in polypropylene composites has been reported in only recently published papers of Panaitescu et al and Stribeck et al 21,22,26 Elastomers with encapsulation ability have been added to composites as compatibilizing agents in small amount (up to 5%) like other compatibilizers. 20 The most recent investigations of the iPP/SiO 2 / SEBS composites with PP-g-MAH added as compatibilizer by Panaitescu et al confirmed relatively good compatibility of the iPP/SEBS interface resulting in improvement of mechanical and dielectrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…are they inside or outside of dispersed elastomeric SEBS particles. 21,26 Accordingly, El-Midany and Ibrahim introduced in polypropylene filled with 3% white microsilica sand as mineral filler 2.5% and 5% of SEBS and SEBS-g-MAH. 21,22 The location of filler and interactions played again the crucial role in determing the propereties of such composite systems.…”
Section: Introductionmentioning
confidence: 99%